Planning land disposal, a comparison between Malaysia & Brunei - Awang, Adibah (2009)
s.5 of the National Land Code 1965 defined "disposal" as any disposal of land made by the State Authority in the exercise of any of the powers conferred by section 42 or of any of the corresponding powers conferred by any previous land law.